Price Setting and Rapid Technology Adoption: The Case of the PC Industry - Copeland, Adam; Shapiro, Adam Hale (The Review of Economics and Statistics, 2016)
We examine how the confluence of competition and upstream innovation influences downstream firms’ profit-maximizing strategies. We focus on personal computers and use two novel data sets to describe the dramatic fall in both price (27% at an annual rate) and sales of a computer over its product cycle. Further, we document that computers are typically sold for only four months before being replaced by a higher-quality product. To explain these facts, we develop and calibrate a vintage capital model that combines a competitive market structure with an exogenous rapid rate of innovation.